The educational contents extracted from the verses indicating moderation in the religious aspect - Albadi, Munira Fahad (Journal of Educational and Psychological Sciences, 2021)
One of God’s blessings and honor for this ummah, may He be glorified and exalted, is to make it a nation that sets out to organize its life through the noble Islamic approach based on mediation. (we made you a nation in the middle) (Al-Baqarah: 143). Moderation mean its safety from excess and negligence. The principle that Islamic education sought to achieve is the subject presented for study under the title of educational contents deduced from the verses indicating moderation. The Almighty said: (God has witnessed that there is no god but He and the angels, and that knowledge was first established with equity, there is no god but He, the Mighty, the Wise) (Al-Imran: 18). The Islamic religion is mediating in its teachings between two opposing or opposing parties, neither excessive nor neglecting its legislations and principles, but rather it is based on equity.